ADSORÇÃO E FOTOCATÁLISE DA NIMESULIDA E DO 17-ESTRADIOL EM SOLUÇÕES AQUOSAS POR CARVÃO ATIVO DECORADO COM FERRITA NANOESTRUTURADA - Finger, Marcel Goulart (2016)
This work aimed to investigate the adsorption and photocatalysis of solutions containing nimesulide and 17β-estradiol with a composite formed of active charcoal decorated with NiFe2O4 nanoparticles. The composite was prepared by the hydrothermal method using Ni (NO3)2 6H2O and Fe(NO3)3 9H2O as precursors solubilized in basic aqueous medium. The solution was sealed in a Teflon reactor and heated 463.15 K for 10 h. The composite was characterized by X-ray diffraction, the morphology was observed by scanning electron microscopy and the with the vibrating sample magnetometer. Nimesulide and 17β-estradiol adsorb according to a pseudo-second order kinetics. The calculation of the thermodynamic parameters of adsorption indicated that the adsorption of nimesulide occurs in an endothermic, spontaneous and favorable manner in all temperatures investigated. The adsorption enthalpy magnitude between the nimesulide and the active charcoal decorated with ferrite is 90.2 kJ mol-1 which indicates that the adsorption is endothermic and occurs through chemisorption. The initial concentration of nimesulide decays by 70% and the concentration of 17β-estradiol decays by 99% after 60 min of UV light irradiation.